Cardiopulmonary (No Ventilation) and Anesthetic Effects of Dexmedetomidine–Tiletamine in Dogs - Zhang, Zhiheng; Du, Xueman; Bai, Hui; Shen, Meilun; Ma, Xiangying; Li, Rouqian; Jin, Xiaodi; Gao, Li (Frontiers in Veterinary Science, 2021)
The aim of the present study was to evaluate the anesthetic and cardiopulmonary effects of dexmedetomidine in combination with tiletamine (without zolazepam) as a general anesthetic. The study was divided into two phases. In Phase 1, eighteen adult healthy mixed-breed dogs were randomly allocated into three groups: Group TD8 (4.5 mg kg-1 tiletamine and 8 μg kg-1 dexmedetomidine), Group TD10 (4.5 mg kg-1 tiletamine and 10 μg kg-1 dexmedetomidine), or Group TD12 (4.5 mg kg-1 tiletamine and 12 μg kg-1 dexmedetomidine). After drug administration, the heart rate (HR), respiratory rate (fR), mean arterial pressure (MAP), systolic arterial pressure (SAP), diastolic arterial pressure (DAP), peripheral hemoglobin oxygen saturation (SpO2), behavioral score, quality of induction and recovery, extent of ataxia, and the time taken for induction and the duration of anesthesia were recorded. The recovery time and quality were recorded after administration of atipamezole (50 μg kg-1) after 60 minutes. In phase 2, the feasibility of combining dexmedetomidine (10 μg kg-1) and tiletamine (4.5 mg kg-1) as general anesthetics was evaluated in dogs (n = 6). HR, fR, MAP, SAP, DAP, Temperature, SpO2, behavioral scores, and adverse reactions were recorded during each surgical procedure. In phase 1, the dogs were anesthetized for 5 minutes after administration of drugs and achieved a maximum behavioral score in TD10 and TD12 after 10 min. Although HR, MAP, SAP, DAP, and NIBP decreased in all three groups, they remained within the normal range. In phase 2, orchiectomy was completed smoothly in all dogs with little fluctuation in the physiological variables. We found that a combination of tiletamine (4.5 mg kg-1) and dexmedetomidine (10 μg kg-1) administered intramuscularly induced moderate anesthesia in dogs and could be utilized for short-term anesthesia and minor surgery.